Answer:
29.98332
Step-by-step explanation:
Its 10^3 = 1000
10^3 = 10*10*10
Answer:
Step-by-step explanation:
-5 - 2(3x - 4) = 3(x - 4) + 6
-5 - 6x + 8 = 3x - 12 + 6
-6x + 3 = 3x - 6
3 = 9x - 6
9 = 9x
1 = x
Answer:
D. 3(x-1) = 3x-3
Step-by-step explanation:
I'm sure that's the answer
Answer:
A. (5,5)
Step-by-step explanation:
- Plug in (5,5) for the x and y values according to the ordered pair. In this case the equation should turn out like this :5 ≤ 5²- 4(5) + 2
- Simplify the equation : 5 ≤ 25 - 20 + 2
- 5 ≤ 7
- A is the answer because it satisfies the inequality as 5 is less than or equal to seven. Though, in this case it is just less than, but not equal to.